From rural scholar to health care professional - A. Ross (South African Family Practice)
Background: International studies have shown that the best strategy for the long-term staffing of rural facilities is the recruitment and training of students of rural origin. However, the crisis in education in South Africa means that these rural students are the least likely to access institutions of higher learning to train as healthcare professionals (HCPs). The aim of this study was to explore the educational experiences of six HCPs of rural origin working in rural areas.